2022
DOI: 10.1101/2022.10.30.514183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population genomic evidence of adaptive response during the invasion history ofPlasmodium falciparumin the Americas

Abstract: Plasmodium falciparum, the most virulent agent of human malaria, spread from Africa to all continents following the out-of-Africa human migrations. During the transatlantic slave trade between the 16th and 19th centuries, it was introduced twice independently to the Americas where it adapted to new environmental conditions (new human populations and mosquito species). Here, we analyzed the genome-wide polymorphisms of 2,635 isolates across the currentP. falciparumdistribution range in Africa, Asia, Oceania, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
0
0
0
Order By: Relevance
“…French Guiana is located within the Guiana Shield region of South America and harbors a low P. falciparum endemicity that is concentrated in remote regions, particularly sites connected with gold mining (Musset et al 2014;Douine et al 2020). Movement of people and parasites throughout the Guiana Shield is well documented (Douine et al 2017;Mathieu et al 2021) and previous genetic clustering analyses of South American P. falciparum have shown that the Guiana Shield region harbors a genetically distinct parasite population (Yalcindag et al 2012;Carrasquilla et al 2022;Lefebvre et al 2023). P. falciparum gene flow therefore occurs across a region that is exposed to the varied public health measures in Brazil, French Guiana, Suriname, Guyana, and Venezuela (Sanna et al 2024).…”
Section: Change In Frontline Drug Did Not Reverse the High Prevalence...mentioning
confidence: 99%
“…French Guiana is located within the Guiana Shield region of South America and harbors a low P. falciparum endemicity that is concentrated in remote regions, particularly sites connected with gold mining (Musset et al 2014;Douine et al 2020). Movement of people and parasites throughout the Guiana Shield is well documented (Douine et al 2017;Mathieu et al 2021) and previous genetic clustering analyses of South American P. falciparum have shown that the Guiana Shield region harbors a genetically distinct parasite population (Yalcindag et al 2012;Carrasquilla et al 2022;Lefebvre et al 2023). P. falciparum gene flow therefore occurs across a region that is exposed to the varied public health measures in Brazil, French Guiana, Suriname, Guyana, and Venezuela (Sanna et al 2024).…”
Section: Change In Frontline Drug Did Not Reverse the High Prevalence...mentioning
confidence: 99%